Environmental, economic and exergetic sustainability assessment of power generation from fossil and renewable energy sources. (14th April 2018) - Stougie, Lydia; Giustozzi, Natalìa; van der Kooi, Hedzer; Stoppato, Anna
Summary: Energy conversion systems have assumed a crucial role in current society. The threat of climate change, fossil fuel depletion and the growing world energy demand ask for a more sustainable way of electricity production, eg, by using renewable energy sources, by improving the conversion efficiency and/or by controlling power plant emissions. Despite the relationship between exergy and sustainability stated in literature, exergy losses are usually not considered when comparing systems and energy sources for power generation. The exergetic sustainability assessment method named Total Cumulative Exergy Loss (TCExL) has been used to assess several systems for electricity production, ie, a coal‐fired power plant, a coal‐fired power plant including carbon capture and storage, a biomass‐fired power plant, an offshore wind farm and a photovoltaic park. The results of the TCExL method have been compared with an environmental sustainability indicator, ie, the overall ReCiPe endpoint indicator and the economic indicator named Present Worth Ratio. The offshore wind farm is the best system from the exergetic and environmental point of view. The photovoltaic park is the system with the second‐best scores. However, from the economic viewpoint including subsidy by the Dutch government, the photovoltaic park performs better than the wind farm system and the system that performs best is the biomass‐fired power plant. Without subsidy, only the coal‐fired power plant without carbon capture and storage is profitable. The exergetic sustainability scores of the coal‐fired and biomass‐fired power plants are similar, but from the environmental sustainability viewpoint, the biomass‐fired power plant performs better than both coal‐fired power plants. As the results of environmental and economic sustainability assessments strongly depend on models, weighting factors, subsidy, market prices, etc, while the results of the exergetic sustainability assessment do not, it is recommended that the exergetic sustainability be taken into account when assessing the sustainability of power generation and other technological systems. Abstract : The sustainability of a coal‐fired power plant, a coal‐fired power plant including carbon capture and storage, a biomass‐fired power plant, an offshore wind farm and a photovoltaic park is assessed from a life cycle point of view. The indicators used for the environmental, economic and exergetic sustainability assessment are ReCiPe endpoint indicators, the Present Worth Ratio and the Total Cumulative Exergy Loss (TCExL), respectively.